The Impacts of E-Commerce to Regional Integration in Southeast Asia - Sukmawani Bela Pertiwi; Amalia Sustikarini; Paramitaningrum Paramitaningrum (Parahyangan Center for International Studies, 2019)
ABSTRACTThis paper aims to examine the social impacts of e-commerce on regional integration in Southeast Asia. This paper argues that the existing literature takes for granted the positive relations between trade and regional integration; define narrowly regional integration in economic terms; and thus, focus mainly on economic impacts of e-commerce to regional integration in Southeast Asia. In contrast to this existing view, regional integration envisioned by ASEAN is not only economic but also social, emphasizing the development of a sense of belonging among regional members. In addition, the logics of the business sector, including e-commerce, may or may not be in line with the logics of ASEAN in imagining regional integration, and thus giving a possibility for the convergence or divergence of interests between the two. Applying constructivist approach on how imagination and transaction contribute to promoting region-ness among regional members, this paper finds that the imagination and transaction of e-commerce actors in the region has not had significant social impact to regional integration and may even develop risk of widening the gap among Southeast Asian countries as the imagination and transaction of many of the e-commerce actors in Southeast Asia are concentrated in the more developed parts of the region.Keywords: E-Commerce, Regional Integration, Southeast Asia, Constructivism